2009
DOI: 10.1038/nature07940
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of radiation-induced changes in human gene expression

Abstract: Humans are exposed to radiation through the environment and in medical settings. To deal with radiation-induced damage, cells mount complex responses that rely on changes in gene expression. These gene expression responses differ greatly between individuals 1 and contribute to individual differences in response to radiation 2 . Here we identify regulators that influence expression levels of radiation-responsive genes. We treated radiation-induced changes in gene expression as quantitative phenotypes 3,4 , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(181 citation statements)
references
References 30 publications
5
176
0
Order By: Relevance
“…Further, increased levels of the cytokine transforming growth factor beta (Tgf-β) in lung tissue have been implicated in the development of fibrosis in animal models [49], including in response to irradiation [50] and specific candidate genes identified in our analysis (Cdkn1a or p21, Pin1) have been demonstrated to influence fibrosis development by altering Tgf-β levels [51,52]. Finally, among the identified candidate genes Shprh is known to function in DNA repair [53], therefore variation in cellular radiation sensitivity such as reported by others [27,54], in addition to strain specific tissue responses to radiation injury, may contribute to the development of the fibrosis phenotype.…”
Section: Discussionmentioning
confidence: 54%
“…Further, increased levels of the cytokine transforming growth factor beta (Tgf-β) in lung tissue have been implicated in the development of fibrosis in animal models [49], including in response to irradiation [50] and specific candidate genes identified in our analysis (Cdkn1a or p21, Pin1) have been demonstrated to influence fibrosis development by altering Tgf-β levels [51,52]. Finally, among the identified candidate genes Shprh is known to function in DNA repair [53], therefore variation in cellular radiation sensitivity such as reported by others [27,54], in addition to strain specific tissue responses to radiation injury, may contribute to the development of the fibrosis phenotype.…”
Section: Discussionmentioning
confidence: 54%
“…A number of studies surveyed transcriptional genotype-byenvironment interactions in humans and reported dozens of response eQTLs in vitro under a variety of environmental challenges such as radiation (26) and treatment with various agents (27)(28)(29). The number of interacting loci in response to malaria infection in our in vivo study is lower than the number of response eQTLs reported in these studies despite the fact that similar sample sizes were used.…”
Section: Resultsmentioning
confidence: 74%
“…Indeed, an alternative approach used to identify cis-interactions (i.e., response-eQTL) is to consider variation in the magnitude of the shifts in gene expression after a treatment, in our case MTB infection, as the quantitative trait to be mapped (33,34). Supporting our previous findings, MTB-response eQTL identified using this approach (Dataset S3) were also significantly enriched for GWAS P values <0.05 (1.8-fold enrichment, χ 2 test, P = 0.01; Fig.…”
Section: Immune Response Eqtl Are Enriched For Susceptibility Genes Fmentioning
confidence: 99%